The role of digital/online resources in the Jewish Diaspora communities - Winer, Dov (Circumscribere International Journal for the History of Science, 2019)
Globalization, in its earlier stages, was expected to erode national and ethnic identities. In contrast, ethnicity and ethnic affiliations persisted, growing socially and politically. This paper examines the role of the globalizing new communications technologies on this process, focusing on Diasporas. The study of trans-state networks based on ethnic solidarity, connections and affinities in the framework of social and political science is quite recent. Following a clarification of the distinction between classical and modern Diasporas we analyse a particular case study, that of the Jewish Diaspora. This diaspora was an early adopter of computer-based communications and the Internet for a wide range of purposes. Early events are described including the diffusion of the Internet to Israel, the planning of a Global Jewish Information Network, Israel 2020 macro scenarios for Israel and the Jewish People and the decision on Jewish Peoplehood through communication technologies. A survey of historical systems (Responsa, BBS, and Usenet) follows by a description of the Jewish population and the wide variety of Jewish Web based activities today. These include the Institutional landscape; Jewish media — press, radio, video and blogs; the impact on Jewish religious observance; Jewish genealogy; Online dating; Social networks; Jewish education; Online learning; Jewish Studies and Digital Humanities; Jewish memory. Judaica Europeana supports the activities previously described by aggregating and facilitating the access and the re-use of Jewish digital culture. Europeana is the leading global digital library for cultural heritage as well as a lively eco-system for relevant stakeholders.